2000
DOI: 10.1002/(sici)1097-0223(200003)20:3<186::aid-pd776>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Co‐variables in first trimester maternal serum screening

Abstract: The objective of this study was to determined the influence of maternal weight, maternal smoking habits, gravidity, parity and fetal gender on the level of maternal serum marker used in first trimester screening for Down syndrome. A total of 2449 singleton unaffected pregnancies from two centres were studied. Maternal serum free beta-human chorionic gonadotrophin (hCG) and alpha-fetoprotein (AFP) concentrations had been measured in all pregnancies, and pregnancy associated plasma protein (PAPP)-A levels had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
43
2
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 0 publications
17
43
2
3
Order By: Relevance
“…This discrepancy in comparison to our study could be explained by the difference in gestational age and the possible placental compensatory action (reduced PAPP-A levels in early pregnancy but not thereafter) which has been observed in the case of Down syndrome [17] as well as PE [11]. Moreover, the definition of smoking is not given in the mentioned study [16] and could have been less strict than ours (one or more cigarettes per day).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This discrepancy in comparison to our study could be explained by the difference in gestational age and the possible placental compensatory action (reduced PAPP-A levels in early pregnancy but not thereafter) which has been observed in the case of Down syndrome [17] as well as PE [11]. Moreover, the definition of smoking is not given in the mentioned study [16] and could have been less strict than ours (one or more cigarettes per day).…”
Section: Discussionmentioning
confidence: 88%
“…For SP1 and, interestingly, for activin A, this absence of an effect by smoking has not been mentioned in the literature so far. For PAPP-A, a difference (slight but significant reduction to 0.89 MoM) has been reported for smokers in the first trimester in a large study [16]. This discrepancy in comparison to our study could be explained by the difference in gestational age and the possible placental compensatory action (reduced PAPP-A levels in early pregnancy but not thereafter) which has been observed in the case of Down syndrome [17] as well as PE [11].…”
Section: Discussionmentioning
confidence: 99%
“…De Graaf et al [8] observed, in women with more than one pregnancy, lower AFP, higher PAPP-A (albeit statistically non-significant) and no effect on free b-hCG.…”
Section: Screening For Chromosome Abnormalities First Trimester Of Prmentioning
confidence: 84%
“…Hence, there was a statistically significant decrease of 1-2% in the detection rate (DR) in pregnancies with female foetuses. Neither De Graaf et al [8] or Ardawi et al [9] found any differences in PAPP-A levels in relation to foetal gender.…”
Section: Screening For Chromosome Abnormalities First Trimester Of Prmentioning
confidence: 99%
“…On the other hand, we could not demonstrate an effect of maternal smoking on the serum levels of activin A, PAPP-A, SP1, HPL, leptin, sE-selectin, IGF-BP1, M-CSF, and VEGF at 17 weeks of gestation, and this was not influenced by the possible later development of pre-eclampsia [57]. For PAPP-A, there is a conflicting report of a slight but significant reduction (to 0.89 MoM) in the literature for smokers' levels in the first trimester [58]. The discrepancy could be explained by the different gestational age of the study populations together with the possible placental compensary action mentioned above [54].…”
Section: Second-trimester Screeningmentioning
confidence: 98%